The beast you are : stories - Tremblay, Paul (William Morrow, an imprint of HarperCollinsPublishers, 2023)
"Paul Tremblay has won widespread acclaim for illuminating the dark horrors of the mind in novels and stories that push the boundaries of storytelling itself. The fifteen pieces in this brilliant collection are all monsters of a kind, ready to loudly (and lovingly) smash through your head and into your heart. In "The Dead Thing," a middle-schooler struggles to deal with the aftermath of her parents' substance addictions and split. One day, her little brother claims he found a shoebox with "the dead thing" inside. He won't show it to her and he won't let the box out of his sight. In "The Last Conversation," a person wakes in a sterile, white room and begins to receive instructions via intercom from a woman named Anne. When they are finally allowed to leave the room to complete a task, what they find is as shocking as it is heartbreaking. The title novella, "The Beast You Are," is a mini epic in which the destinies and secrets of a village, a dog, and a cat are intertwined with a giant monster that returns to wreak havoc every thirty years."--